2000
DOI: 10.1093/jn/130.11.2658
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Glucosides Are Completely Hydrolyzed in Ileostomy Patients before Absorption

Abstract: Flavonoids, dietary components in vegetables, fruits and beverages, may protect against coronary heart disease, stroke and cancer. However, the bioavailability of these compounds is questionable. A previous study in ileostomy patients of the most abundant flavonoid, quercetin, suggested a 52% absorption of its major dietary forms, monoglucoside (QMG) and diglucoside (QDG), from an onion meal. However, this was based on indirect measurements after acid hydrolysis. Because human intestinal Caco-2 cell monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(91 citation statements)
references
References 30 publications
3
86
0
Order By: Relevance
“…23) The question regarding the route of the flavonoid when are absorbed remains unsettled. Walle et al (2000) 24) found that both major glucosides of quercetin in the onion, quercetin-monoglucoside and quercetin-diglucoside, are hydrolyzed in the human small intestine to the aglycon quercetin, 65-81% of which is then presumably absorbed. Many other researchers have confirmed that after eating foods containing quercetin glycoside or quercetin aglycon, quercetin presented as the glucuronide or sulfate form or further as methylated forms, these were conjugated to glucuronide or sulfate in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…23) The question regarding the route of the flavonoid when are absorbed remains unsettled. Walle et al (2000) 24) found that both major glucosides of quercetin in the onion, quercetin-monoglucoside and quercetin-diglucoside, are hydrolyzed in the human small intestine to the aglycon quercetin, 65-81% of which is then presumably absorbed. Many other researchers have confirmed that after eating foods containing quercetin glycoside or quercetin aglycon, quercetin presented as the glucuronide or sulfate form or further as methylated forms, these were conjugated to glucuronide or sulfate in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…38 ). Some fl avonoid glycosides could be hydrolyzed in the small intestine 39 . If the fl avonoid glycosides are able to enter the intestinal epithelial cells (enterocytes), which may include shredded cells, they may be hydrolyzed by broadspecifi c β-glucosidase (BSβG) (ref.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Although the intestinal absorption and metabolism of ingested quercetin glycosides has been uncertain, substantial previous evidence has suggested that the main pathway is their conversion to conjugate metabolites through aglycone by deglycosylation activity and subsequent conjugation activity. [16][17][18][19][20][21][22][23][24][25][26][27] Moreover, conjugated metabolites of quercetin have recently been found to exhibit antioxidative properties toward lipid peroxidation in vivo and in vitro. 18,19,22,24,26,28) It has been shown that the e‹ciency of intestinal absorption of quercetin is aŠected by its solubility in the vehicle used for administration.…”
mentioning
confidence: 99%